The Use of Artificial Intelligence as a Marketing Support Tool: A Feasibility Study of the Chatbot “TANYA” Use on Consumer Behavioral Intention in Indonesia - Abyantoro, Muhammad Farras (Dinasti Publisher, 2026)
The features of a chatbot can lead to behavioral intention among its users. This study examines how the features found in TANYA can generate behavioral intention to its consumers. This study uses several different research variables which are then made into a model with a simple regression design. These variables are convenience, authenticity of conversation, enjoyment, pass time, social influence, anthropomorphism, privacy concern, and immature technology. The study was conducted quantitatively through Google Form and successfully gathered 214 respondents from Generation Z and millennials who had used TANYA previously. Using linear regression analysis through SPSS, the study concludes that convenience, enjoyment, social influence, anthropomorphism, and immature technology influence the behavioral intention experienced by consumers, while authenticity of conversation, pass time, and privacy concern have no influence on behavioral intentions of TANYA consumers.